The Impact of Customer Relationship Management on Caller Satisfactions in Customer Contact Centers: Evidence from Malaysia - Abdullateef, Aliyu Olayemi (2011)
Available literatures have established customer relationship management (CRM) as giving opportunity to both internal and external customers of an organization in exploring critical information through the integration of company’s telephone system, chat groups, Interactive voice response, facsimile transmission, electronic data interchange, voice over internet, web sites and e-mail touch points that will result in satisfying customer self services for new product purchases, assist in up-selling and cross selling and creating customer loyalty, value and profitability. Despite the enormous increasing acknowledgement of CRM importance, very little studies have focused on the impact of CRM applications on inbound customer contact center performance. This empirical research explored the relationship between CRM dimensions, first call resolutions, perceived service quality and caller satisfactions within the inbound call centers. A conceptual framework was developed based on the extant literatures and information that were obtained from initial interviews with call center managers. The research model incorporated key CRM constructs; customer orientation, CRM organization, knowledge management and technology based CRM and also investigated the impact of these dimensions on first call resolution (FCR), perceived service quality and caller satisfaction. Importantly, FCR and perceived service quality were considered as critical antecedents to caller satisfaction. In this quantitative study, a survey of 168 call center managers in Malaysia was analyzed through structural equation modeling, constituting an overall 43.3% response rate. The research findings indicated that out of the four hypothesized positive relationship between CRM dimensions and caller satisfaction, three were supported. The findings also indicated that first call resolutions have significant influence on caller satisfactions. Key benefits for practitioners and academia was finally discussed under the theoretical and practical implications, while necessary suggestions on new area of research were recommended for future researchers.